PENGEMBANGAN SISTEM PEMANTAUAN KUALITAS AIR UNTUK MEMANTAU AIR LIMBAH INDUSTRI SECARA ONLINE - Yudo, Satmoko (Center for Environmental Technology, 2016)
The number of industry in Indonesia continues to increase along with the increase in population. The increase in the construction industry will have a positive impact as increasing social and economic life of society. However, the negative impact is the increasing environmental pollution such as air pollution, water pollution and soil. One of the causes of water pollution industrial waste discharged into water bodies without treatment beforehand. Various attempts have been made by the government for the supervision and control of water pollution by issuing laws and regulations, permit to dispose of liquid waste and Proper Program. Nevertheless, there are still companies and industries that discharge wastewater does not meet the requirements is allowed. One effort in monitoring, particularly in the waste disposal industry by applying online monitoring in real-time at the outlet WWTP Industry. This technology is expected to real-time monitoring can be done by government agencies (Ministry of Environment and Forestry and the Regional Environmental Agency) and can send an early warning when there is pollution. This monitoring system generally consists of sensors, data loggers, data communications and data centers. Sensor data from industrial wastewater outlet will be sent to the data center continuously, then the data will be stored and processed by database system and then displayed on Internet.Ã‚Â Keyword : industrial wastewater pollution, online monitoring, wastewater quality, WWTP